Pinang City Bus Terminal Neo-Vernacular Architectural Themes - Darwin Sinabariba; Isniar Tiurma Leonora Ritonga; Shienny Wijaya Putri (CV. Inara, 2021)
Bus Terminals help facilitate land transportation activities in the distribution of passengers in a city. Bus Terminal provides services for the general public with the aim of access, mobility and land transportation that are often used by humans to travel. The existence of the terminal is very vital in the implementation of public transportation because in the terminal there is a meeting between service providers and service users, places to raise and drop off passengers at the beginning and end of public transport travel, as well as public transport vehicle crew rest. Bus Terminal in South Labuhanbatu Regency uses Post-Modern Architecture design in its planning and design, it is expected that with modern building design can give a dynamic and unique impression.